Working‐age people with disability and labour force participation: Geographic variations in Australia. Issue 3 (17th September 2019) - Zhou, Qingsheng; Llewellyn, Gwynnyth; Stancliffe, Roger; Fortune, Nicola
Abstract: To examine geographic variation in labour force participation rate (LFPR) of working‐age people with disability in Australia and associated factors. This study uses Australian Census 2016 data at Statistical Area Level 2 (SA2) and engages multiple linear regression to explore the relationship between the dependent variable, = LFPR of people with disability, and diverse independent variables that reflect collective characteristics of people with disability and their non‐disabled peers within SA2. While LFPRs for people with disability varied greatly by SA2, people with disability had considerably lower LFPR than their non‐disabled peers in all areas. The LFPRs tended to be higher in SA2s with higher percentages of people with disability who had completed year 12 or gained post‐school education, with higher household income, and where a higher proportion of people with disability mainly spoke English at home. These results indicate that where people live matters. Geographic variation in LFPR for people with disability is associated with geographic variation in their educational attainment and other social and community characteristics of the areas in which they live. This study contributes towards gaining a more sophisticated and nuanced understanding of the factors that influence LFPR of people with disability in relation to their local community environment.